2010
DOI: 10.1007/s00404-010-1506-1
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical and fetal outcomes of a new management strategy in patients with intra-hepatic cholestasis of pregnancy

Abstract: The incidence of ICP in this region is low compared to worldwide range. Expectant management to 40-weeks gestation is associated with obstetrical and fetal outcomes comparable to normal pregnancy; however, intrapartum fetal asphyxia is more likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 32 publications
1
38
1
2
Order By: Relevance
“…Older studies of ICP demonstrated a clustering of stillbirths associated with the condition at 37-39 weeks of gestation ( Figure 2); [2][3][4]12,14,16,[34][35][36][37][38][39][40][41][42][43][44][45] therefore, elective early delivery was suggested to help protect against this risk. There has been no adequately powered trial to evaluate the effect of elective early delivery; however, the implementation of this practice appeared to correlate with a reduction in the reports of stillbirth, although this could be attributed to other reasons (for example, other changes in antenatal management, early publication bias).…”
Section: Elective Early Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Older studies of ICP demonstrated a clustering of stillbirths associated with the condition at 37-39 weeks of gestation ( Figure 2); [2][3][4]12,14,16,[34][35][36][37][38][39][40][41][42][43][44][45] therefore, elective early delivery was suggested to help protect against this risk. There has been no adequately powered trial to evaluate the effect of elective early delivery; however, the implementation of this practice appeared to correlate with a reduction in the reports of stillbirth, although this could be attributed to other reasons (for example, other changes in antenatal management, early publication bias).…”
Section: Elective Early Deliverymentioning
confidence: 99%
“…Graphs showing the gestational week of stillbirths associated with ICP [2][3][4]12,14,16,[34][35][36][37][38][39][40][41][42][43][44][45]. (a) ICP-associated stillbirths tend to cluster around 37-39 weeks of gestation.…”
mentioning
confidence: 99%
“…It was reported that there is a wide geographic and ethnic variation of ICP in many studies worldwide. Interestingly, in the following years, the prevalence of disease has markedly decreased in some regions (13,14). The incidence found in the current study was comparable to the others conducted in the United States and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…71 Suudi Arabistan'da yapılmış olan 76 hastanın dâhil edildiği bir çalışmada; son zamanlarda GİK tanısı alan gebelerde, normal gebelerden (güven vermeyen NST ve mekonyum pasajı dı-şında) farklı olarak olumsuz fetal sonuçların izlenmediği bildirilmiştir. 77 Tedavi ise aktif veya ekspektan olarak uygulanabilmektedir. Ekspektan yönetimde kötü fetal sonuçlar izlenebilmektedir.…”
Section: Gebeli̇ği̇n İntrahepati̇k Kolestazinda Hasta Yöneti̇mi̇unclassified